Will preoperative trials change future clinical practice?. (January 2011) - Lim, Elgene; Winer, Eric P
Preoperative systemic therapy (PST) has emerged from an infrequently used approach in the management of patients with breast cancer to one with an established role in both inoperable and operable breast cancer. In particular, it now has an established role in drug development and biomarker discovery programs. In this era of molecular-based therapies, the unique resource of paired pre- and post-treatment tissue in PST trials represents a powerful research tool for the in vivo study of biologic mechanisms of systemic therapy. It is possible to examine downregulation of signaling pathways that are known to be activated, and off-target effects through the identification of pathways not previously known to be activated. In addition, correlative studies may identify predictive biomarkers of response and resistance, which has the potential to inform the design of larger and more expensive adjuvant trials. The aims of this article are to review key developments in PST trials, particularly in specific breast cancer subtypes, and identify areas in which PST trials can facilitate drug development and rapidly translate its findings into clinical practice.